2014
DOI: 10.4103/0973-7847.134230
|View full text |Cite
|
Sign up to set email alerts
|

Role of complementary and alternative medicine in geriatric care: A mini review

Abstract: Since time immemorial homo sapiens are subjected to both health and diseases states and seek treatment for succor and assuagement in compromised health states. Since last two decades the progressive rise in the alternative form of treatment cannot be ignored and population seems to be dissatisfied with the conventional treatment modalities and therefore, resort to other forms of treatment, mainly complementary and alternative medicine (CAM). The use of CAM is predominantly more popular in older adults and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…The use of CAM is increasing rapidly, now exceeding a prevalence of 53% among those aged 50 years and above in the US [ 19 ]. Traditional Chinese herbal medicine is the most common CAM for the prevention and treatment of dementia in Asian countries.…”
Section: Discussionmentioning
confidence: 99%
“…The use of CAM is increasing rapidly, now exceeding a prevalence of 53% among those aged 50 years and above in the US [ 19 ]. Traditional Chinese herbal medicine is the most common CAM for the prevention and treatment of dementia in Asian countries.…”
Section: Discussionmentioning
confidence: 99%
“…Acceptance and use of complementary and integrative medicine (CIM) therapies is growing, especially among the Baby Boomers cohort born in [1946][1947][1948][1949][1950][1951][1952][1953][1954][1955][1956][1957][1958][1959][1960][1961][1962][1963][1964], and later birth cohorts [1]. CIM has been widely used in many different cultures dating back to the eighteenth century, starting with homeopathy and ancient healing traditions, such as Traditional Oriental Medicine (TOM) (e.g., Traditional Chinese Medicine (TCM), acupuncture, shiatsu, and reiki), Indian systems of healthcare (e.g., Ayurveda and yoga), and Native American healing practices (e.g., Sweat Lodge and Talking Circles).…”
Section: Introductionmentioning
confidence: 99%
“…All integrative practices share the belief that wellbeing is a state of balance in the spheres encompassing the spiritual, physical, and mental/emotional functioning that can be achieved by leading a balanced healthy lifestyle ensured by proper nutrition, exercise, sleep habits, and the ability to regulate stress response via meditation or other mind-body practices. Because CIM is often considered to be a natural and safer option compared to conventional medicine in addressing common health conditions, these interventions are rapidly gaining popularity in the USA [1,2]. Many of these practices fall into the category of lifestyle medicine where individuals are empowered to make healthier choices in diet, exercise, sleep, and stress management.…”
Section: Introductionmentioning
confidence: 99%
“…12,18 Additionally, findings from our study indicated that older patients benefited the most, by receiving CHMs treatment, from lowering the risk of COPD, echoing the findings of an earlier report. 19 Previous research indicated that younger adults are more likely than older adults to gain prompt access to social resources and maintain close proximity to their social network. 20 Younger RA patients, therefore, might more easily adapt to the effects of the progression of RA, thereby diluting the therapeutic effect of CHMs.…”
Section: Discussionmentioning
confidence: 99%